Numerical Simulation of the Stress-Strain State of a Thin Plate in the ANSYS Package as a Two-Dimensional Formulation of the Thermo-Elasticity - Sedelnikov, Andry; Serdakova, Valeria; Nikolaeva, Aleksandra; Evtushenko, Maksim (Applications of Modelling and Simulation, 2023)
This work considers numerical modeling of the stress-strain state of a homogeneous rectangular thin plate after a thermal shock. The presented solution is implemented in the finite element (FEM) package ANSYS Mechanical APDL 2020 R2. The task to be considered is a two-dimensional problem with the initial deflection of the plate. It is considered that the plate is cantilevered only at one end, but the other three edges are free. At the moment of a temperature shock, the plate acquires a curved shape. Within the framework of the heat conduction problem, two heat flows are taken into account. The first flow goes from the surface layer subjected to thermal shock deep into the plate. The second flow spreads parallel to its longitudinal axis. This axis is perpendicular to the plate embedding line. The dependencies of the temperature field of the plate are built. A comparative analysis was carried out with approximate analytical dependencies obtained in other works. The dependencies of the projections of the displacement vector of the plate points are obtained only in the case when the longitudinal displacement is small. There is also an analysis of the applicability of the results for practical purposes. For example, it is proposed to use the results obtained to assess the significance of the impact of thermal shock of solar panels on the motion of a small satellite.